Surgical Management Of Oral Squamous Cell Carcinoma In A Camel (Camelus Dromidarius) - Jena, Biswadeep; Ahmed, Abrar; Pagrut, Nilesh Kumar; Tiwari, R.P.; Mishra , G.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Squamous cell carcinoma (SCC) is a malignant tumour of squamous epithelial cells. It is a common neoplasm affecting all domestoic animals, but most commonly the dog, horse and cat. When SCC occurs in the mouth and throat, it is called oral squamous cell carcinoma (Moulton, 1978). In camel, SCC has been reported frequently on the flank, caudal to the chest pad, side of the hock, the hard palate, nasal cavity, interdigital space and dorsal part of the nail of the foot (Siddiqui and Telfah, 2010). But SCC on cheek mucosal wall has rarely been reported. The present study describes the oral SCC on cheek mucosal wall in a Bikaneri Camel.